Preparation of Entrepreneurs in Kanchanaburi Province for Readiness toward Labor Market in ASEAN Economic Community - Kumkrua, Malinee; Pollachai, Wiyada; Pomso, Supaporn; Jorncharoen, Nirut (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research was conducted for three objectives: (1) to study the readiness of the entrepreneurs in Kanchanaburi Province for entering the ASEAN Community labor market after free labor movement is allowed; (2) to compare four aspects of the readiness of types of business entrepreneurs in terms of personnel, finance or budget, materials and management; and (3) to study the recommendations for the entrepreneurs’ readiness preparation towards ASEAN Community’s labor market entrance. The research sample consisted of 363 entrepreneurs who answered a questionnaire. A focus group of nine representatives selected from different types of business and related organizations was also carried out. The results, overall and in some respective aspects, revealed moderate levels of readiness. The entrepreneurs’ readiness, compared among types of business, was generally found significantly different at a 0.05 level of significance, except in terms of personnel and materials. Suggestions include: The entrepreneurs should be prepared to study laws relating to themselves and their organizations, in order to create clarity in organization management and taxation. They should have knowledge and skills in accounting. And, they should also improve and develop the products and innovations of their own.